EFFECTS OF GROSS FIXED CAPITAL FORMATION AND SELECTED INTERNATIONAL TRADE POLICY INSTRUMENTS ON AGRICULTURAL PRODUCTIVITY IN NIGERIA: AN AUTOREGRESSIVE DISTRIBUTED LAG (ARDL) MODEL APPROACH - Awuna, J. M.; Musa, A. U.; Onah, A. E. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study assessed the agricultural productivity effects of gross fixed capital formation, exchange rate and agricultural tariff. The study utilized secondary data spanning from 1980 to 2022. Augmented Dickey Fuller Test was used to test for stationarity among variables, Johansen Cointegration test was used to test for long run relationship between variables. Vector Error Correction Model was used to analyze the effect of gross fixed capital formation, agricultural tariff and exchange rate on agricultural productivity. The result of the Augmented Dickey Fuller (ADF) test for unit root indicated that the variables agricultural output and gross fixed capital formation were stationary at level while, agricultural tariff and exchange rate became stationary on first differencing. Further investigation into the series properties of the variables through the use of Johansen co-integration mechanism indicates that there was one co-integrating equation among the variables. The results of the ARDL for long-run indicated that Cointegrating equation [CointEq(-1)] was statistically significant and negative (-0.171646) at 1% probability level (p<0.01) indicating a moderate speed of adjustment (that is, the speed at which the deviation from long run equilibrium is adjusted quickly where 0.171 of the disequilibrium is removed immediately in each period). Specifically, the coefficients of inflation rate (-0.103255) and agricultural tariff (-1.110961) were negative and statistically significant at 1% probability level (p<0.01). The study concluded that raising trade policy instruments such as inflation rate and agricultural tariff will negatively affect agricultural productivity. The study therefore recommended that Government should lower tariffs on agricultural goods so as to encourage import and exports within the agricultural sector. This will promote local production and boost productivity.